Simple Field Plot Experiments in Agriculture. Analysis of Variance, LSD, Design and Reporting - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
J van Lidth de Jeude. 1999. 107 pp.ISBN 90 5285 061 5 $15STOASPO Box 78, 6700 AB Wageningen, The Netherlands.Fax: +31 317 424 770Email: int@stoas.nlWebsite: www.stoas.nl/internationaal/publicaties.htm